2014
DOI: 10.1161/circep.114.001938
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Atrial Fibrillation in Patients With Left Ventricular Systolic Dysfunction

Abstract: Background— Catheter ablation of atrial fibrillation (AFCA) is an established therapeutic option for rhythm control in symptomatic patients. Its efficacy and safety among patients with left ventricular systolic dysfunction is based on small populations, and data concerning long-term outcome are limited. We performed this meta-analysis to assess safety and long-term outcome of AFCA in patients with left ventricular systolic dysfunction, to evaluate predictors of recurrence and impact on left ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 42 publications
12
82
1
9
Order By: Relevance
“…U pacjentów, u których HFrEF rozwija się w następstwie AF z szybką czynnością komór (kardiomiopatia tachyarytmiczna), preferuje się strategię kontroli rytmu serca, co opiera się na kilku dość małych kohortach pacjentów oraz badaniach, w których donoszono o poprawie czynności lewej komory po przywróceniu rytmu zatokowego [185,[226][227][228]. Rozpoznanie kardiomiopatii tachyarytmicznej może być trudne, a czasami jego dokonanie wymaga przywrócenia rytmu zatokowego [229].…”
Section: Pacjenci Z Migotaniem Przedsionków Oraz Niewydolnością Sercaunclassified
See 2 more Smart Citations
“…U pacjentów, u których HFrEF rozwija się w następstwie AF z szybką czynnością komór (kardiomiopatia tachyarytmiczna), preferuje się strategię kontroli rytmu serca, co opiera się na kilku dość małych kohortach pacjentów oraz badaniach, w których donoszono o poprawie czynności lewej komory po przywróceniu rytmu zatokowego [185,[226][227][228]. Rozpoznanie kardiomiopatii tachyarytmicznej może być trudne, a czasami jego dokonanie wymaga przywrócenia rytmu zatokowego [229].…”
Section: Pacjenci Z Migotaniem Przedsionków Oraz Niewydolnością Sercaunclassified
“…Rozpoznanie kardiomiopatii tachyarytmicznej może być trudne, a czasami jego dokonanie wymaga przywrócenia rytmu zatokowego [229]. Ablacja przezcewnikowa może być użyteczną metodą poprawy czynności lewej komory i jakości życia u pacjentów z AF i HFrEF [185,[226][227][228], ale potrzebne są dalsze dane. Strategię postępowania u pacjentów z AF i niewydolnością serca podsumowano na rycinie 4.…”
Section: Pacjenci Z Migotaniem Przedsionków Oraz Niewydolnością Sercaunclassified
See 1 more Smart Citation
“…Actualmente existen dos formas de aproximarse al manejo de la FA (1,5,6,8,9,10,12,18,(53)(54)(55)(56)(57)(58)(59) (60); lo cual está respaldado por un metaanálisis reciente de esta estrategia de manejo en pacientes con falla cardiaca, con una tasa de éxito dependiente del tiempo de evolución de la falla cardíaca y el método de ablación utilizado (61). Las características principales de los diferentes métodos de cardioversión y los factores que influencian su elección se escapan del alcance de este artículo y se remite al lector a sus estudios fundamentales (60-65), revisiones (8, 14, 56, 58, 64-68) y a las guías de manejo de FA (1, 5, 9, 10) para obtener dicha información.…”
Section: Tratamientounclassified
“…In recent years, catheter ablation (CA) has provided a novel direction for the treatment of HF complicated with AF, based on its advantages in the restoration of sinus rhythm, improvement of cardiac function and long-term prognosis (5). However, one previous meta-analysis study demonstrated that the ablation success rate of HF patients with AF is only ~60% (6). Therefore, how to reduce the recurrence rate of AF with HF has become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%